Plethysmographic variability index as a predictor of propofol-induced hypotension: A prospective observational study - Joseph N Paul; Rashmi Rani; Joachim, Nayanthara; Apoorwa N Kothari (Asian Journal of Medical Sciences, 2025)
Background: Propofol as an intravenous (IV) induction agent frequently causes significant hypotension and requires monitoring and prompt intervention. The plethysmographic waveform, obtained from a pulse oximeter, relies on two components of light absorption-red and infrared, representing changes in blood volume and cardiovascular status of the patient. Aims and Objectives: The current study aimed to obtain a baseline value and positive predictive value (PPV) of plethysmographic variability index (PVI) to predict hypotension and also compare the PPV of PVI and perfusion index (PI) to predict hypotension induced by propofol. Materials and Methods: Seventy patients posted for elective surgery were first given IV crystalloids 2 h before surgery and then induced with propofol IV. Hemodynamic parameters, PI and PVI were recorded from baseline until 3 min post-intubation. Hypotension was defined as a fall in systolic blood pressure >30% or mean arterial pressure (MAP) <60 mmHg. Patients were then grouped into those who developed hypotension (Group H) and those who did not (Group NH). Statistical analysis of MAP, PVI, and PI was done. Receiver operating characteristic (ROC) curves were plotted and analyzed. The PPV of PVI and PI was calculated and compared. Results: Hypotension occurred in 56 patients. The mean baseline MAP was lower in Group H (91.3±10.54 mmHg vs. 99.93±3.36 mmHg). The fall in MAP was highest at 3 min post-induction (Group H 59.38±7.09, Group NH 79.36±8.05). The difference in baseline PVI was not statistically significant (Group H 15.59±3.67, Group NH 15.43±5.65). PVI peaked in Group H when MAP was minimum (59.38±7.09 mmHg) at 3 min post-induction. The difference in baseline PI was not significant at any time point (Group H 1.13±1.02, Group NH 0.92±0.47) Area under the ROC curve of 0.534 for PVI and 0.559 for PI were not statistically significant hence showing no correlation between baseline PVI and PI and propofol-induced hypotension. Conclusion: Baseline PVI and PI can serve as screening tools and not diagnostic tools for predicting hypotension. Baseline PVI ≥19 is more accurate to predict post-induction hypotension than the values mentioned in previous studies.